La creación del lenguaje cinematográfico - Cerda Ortiz, Karen Daniela (2020)
Film is an art that consists of different resources and materials, it is a team work and contains a great variety of jobs within a production. The director is a very important figure in film; creates the cinematographic language and guides the creative process of a film. The director prolongs or condenses time, weaves the sequences, gives meaning to the images, opens the mind of a viewer to multiple and varied interpretations. Alfred Hitchcock and Michael Haneke managed to create their own language. Hitchcock made this through suspense, while Michael Haneke has created his own way of telling stories through realism.